Efektivitas ensiklopedia tumbuhan kontekstual dalam meningkatkan literasi sains dan motivasi belajar siswa sekolah dasar - Maryani, Ika; Rupilu, Aprilia Cyahyani (Universitas Negeri Jakarta, 2025)
The low level of science literacy and student motivation demands innovative, relevant, and engaging learning media. This study aims to measure the effectiveness of a contextual-based plant encyclopedia in improving science literacy and student motivation in elementary schools. This study uses a quantitative method with a quasi-experimental one-group pretest-posttest design. The research population consists of 4th-grade students from SD Kotagede 3, Yogyakarta, with a sample of 20 students selected through simple random sampling. The research instruments include pretest-posttest questions to measure science literacy, Guttman scale questionnaires for learning motivation, as well as observation sheets and interviews to support qualitative data. We analyzed the data using descriptive statistics and the non-parametric Wilcoxon test, as the assumption test results indicated that the data did not meet the criteria for normality and homogeneity. The research results show a significant increase in students' science literacy (p < 0.001), although there was no significant increase in learning motivation (p = 0.492). These findings indicate that context-based encyclopedias are highly effective in supporting students' understanding of science concepts through the presentation of engaging and structured information. However, the minimal impact on learning motivation indicates the need for additional strategies, such as teacher guidance and increased media interactivity. The implications of this research include the integration of context-based encyclopedias as effective learning media and the need for supporting strategies, such as longer intervention durations and teacher guidance for more optimal results.